Value of three-dimensional volume rendering images in the assessment of the centrality index for preoperative planning in patients with renal masses. Issue 1 (January 2017) - Sofia, C.; Magno, C.; Silipigni, S.; Cantisani, V.; Mucciardi, G.; Sottile, F.; Inferrera, A.; Mazziotti, S.; Ascenti, G.
Abstract : Aim: To evaluate the precision of the centrality index (CI) measurement on three-dimensional (3D) volume rendering technique (VRT) images in patients with renal masses, compared to its standard measurement on axial images. Materials and methods: Sixty-five patients with renal lesions underwent contrast-enhanced multidetector (MD) computed tomography (CT) for preoperative imaging. Two readers calculated the CI on two-dimensional axial images and on VRT images, measuring it in the plane that the tumour and centre of the kidney were lying in. Correlation and agreement of interobserver measurements and inter-method results were calculated using intraclass correlation (ICC) coefficients and the Bland–Altman method. Time saving was also calculated. Results: The correlation coefficients were r =0.99 ( p <0.05) and r =0.99 ( p <0.05) for both the CI on axial and VRT images, with an ICC of 0.99, and 0.99, respectively. Correlation between the two methods of measuring the CI on VRT and axial CT images was r =0.99 ( p <0.05). The two methods showed a mean difference of –0.03 (SD 0.13). Mean time saving per each examination with VRT was 45.5%. Conclusions: The present study showed that VRT and axial images produce almost identical values of CI, with the advantages of greater ease of execution and a time saving of almost 50% for 3D VRT images. In addition, VRT provides an integrated perspective that can better assist surgeons in clinical decision making and in operative planning, suggesting this technique as a possible standard method for CI measurement. Highlights: Centrality index is a score that expresses the difficulty of kidney tumour resection. C-index is based on tumour size and its distance from the kidney centre. Volume rendering technique offers a simple and quick way to obtain C-index. VRT provides an integrated perspective helping urologists in pre-operative planning.